Proteomic Analysis Reveals Commonly Secreted Proteins of Mesenchymal Stem Cells Derived from Bone Marrow, Adipose Tissue, and Synovial Membrane to Show Potential for Cartilage Regeneration in Knee Osteoarthritis - Yura Lee; Yo Seph Park; Na Young Choi; Yong Il Kim; Yong-Gon Koh (Stem Cells International)
Paracrine factors secreted by mesenchymal stem cells (MSCs) reportedly modulate inflammation and reparative processes in damaged tissues and have been explored for knee osteoarthritis (OA) therapy. Although various studies have reported the effects of paracrine factors in knee OA, it is not yet clear which paracrine factors directly affect the regeneration of damaged cartilage and which are secreted under various knee OA conditions. In this study, we cultured MSCs derived from three types of tissues and treated each type with IL-1β and TNF-α or not to obtain conditioned medium. Each conditioned medium was used to analyse the paracrine factors related to cartilage regeneration using liquid chromatography-tandem mass spectrometry. Bone marrow-, adipose tissue-, and synovial membrane-MSCs (all-MSCs) exhibited expression of 93 proteins under normal conditions and 105 proteins under inflammatory conditions. It was confirmed that the types of secreted proteins differed depending on the environmental conditions, and the proteins were validated using ELISA. The results of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis using a list of proteins secreted by all-MSCs under each condition confirmed that the secreted proteins were closely related to cartilage repair under inflammatory conditions. Protein-protein interaction networks were confirmed to change depending on environmental differences and were found to enhance the secretion of paracrine factors related to cartilage regeneration under inflammatory conditions. In conclusion, our results demonstrated that compared with knee OA conditions, the differential expression proteins may contribute to the regeneration of damaged cartilage. In addition, the detailed information on commonly secreted proteins by all-MSCs provides a comprehensive basis for understanding the potential of paracrine factors to influence tissue repair and regeneration in knee OA.